Metabolic Disease Programming: From Mitochondria to Epigenetics, Glucocorticoid Signalling and Beyond. (13th June 2021) - Grilo, Luís F.; Tocantins, Carolina; Diniz, Mariana S.; Gomes, Rodrigo Mello; Oliveira, Paulo J.; Matafome, Paulo; Pereira, Susana P.
Abstract: Embryonic and foetal development are critical periods of development in which several environmental cues determine health and disease in adulthood. Maternal conditions and an unfavourable intrauterine environment impact foetal development and may programme the offspring for increased predisposition to metabolic diseases and other chronic pathologic conditions throughout adult life. Previously, non‐communicable chronic diseases were only associated with genetics and lifestyle. Now the origins of non‐communicable chronic diseases are associated with early‐life adaptations that produce long‐term dysfunction. Early‐life environment sets the long‐term health and disease risk and can span through multiple generations. Recent research in developmental programming aims at identifying the molecular mechanisms responsible for developmental programming outcomes that impact cellular physiology and trigger adulthood disease. The identification of new therapeutic targets can improve offspring's health management and prevent or overcome adverse consequences of foetal programming. This review summarizes recent biomedical discoveries in the Developmental Origins of Health and Disease (DOHaD) hypothesis and highlight possible developmental programming mechanisms, including prenatal structural defects, metabolic (mitochondrial dysfunction, oxidative stress, protein modification), epigenetic and glucocorticoid signalling‐related mechanisms suggesting molecular clues for the causes and consequences of programming of increased susceptibility of offspring to metabolic disease after birth. Identifying mechanisms involved in DOHaD can contribute to early interventions in pregnancy or early childhood, to re‐set the metabolic homeostasis and break the chain of subsequent events that could lead to the development of disease.